2012
DOI: 10.4162/nrp.2012.6.6.505
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of andropause symptoms by dandelion and rooibos extract complex CRS-10 in aging male

Abstract: Many aging male suffer various andropause symptoms including loss of physical and mental activities. This study evaluated the putative alleviative effects of CRS-10 dandelion and rooibos extract complex (CRS-10) on the symptoms of andropause. The survival rate of TM3 Leydig cells (TM3 cells) treated with CRS-10 was measured based on typical physiological stress. After daily intake of CRS-10 for 4 weeks, the level of testosterone, physical activity and both the number and activity of sperm in older rats (18 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Recently, Noh et al . () noticed a significant increase in serum testosterone in ageing rats (18 week‐old) after treatment with a mixture of rooibos and dandelion extract. However, it was not investigated which of these plants was responsible for the increase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Noh et al . () noticed a significant increase in serum testosterone in ageing rats (18 week‐old) after treatment with a mixture of rooibos and dandelion extract. However, it was not investigated which of these plants was responsible for the increase.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with dandelion extract (50 µg/mL) increased the cell viability (Noh et al. 2012 ), and further studies are required to establish the potential of this extract for alleviating symptoms of andropause. However, no study has reported the steroidogenic effects of TOE in Leydig cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be attributed to protection and activation of Leydig cells and the production of endogenous testosterone (Noh et al. 2012 ). The mechanism underlying the steroidogenic effect of T. officinale extract (TOE) in mouse Leydig cells has not been studied thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Eweoya, Oyewopo, and Yama () designed at examining the possible impact of the leaf extract of G. brevis on male fertility in adult male rats. Glyphaea brevis is thought to be medicinally useful; its traditional use in reproductive remedies has been reported: these effects may be attributed to protection and activation of Leydig cells and the production of endogenous testosterone (Noh et al, ). The mechanism underlying this effect of Glyphaea brevis twigs extract (GBT) in TM3 Leydig cells has not been studied thus far.…”
Section: Introductionmentioning
confidence: 99%